The Impact of Xenophobic Attacks on the Livelihoods of Migrants in Selected Provinces of South Africa - Rabotata, Enoch; Makhubele, Jabulani; Baloyi, Themba; Mafa, Prudence; Kwakwa, Motshidisi; Masilo, Tuelo; Matlakala, Frans; Mabasa, Allan (International Journal of Criminology and Sociology, 2021)
Migration and xenophobia are realities that cannot be ignored globally. Recently, there has been a plethora of xenophobic attacks as a result of structural and socio-economic conditions in South Africa. This paper aimed to establish the impact of xenophobic attacks on the livelihoods of migrants in selected provinces of South Africa. Researchers opted for a qualitative study using a case study design. Participants were drawn from the population in Limpopo, North-West and Mpumalanga Province. A snowball sampling technique was used to sample seven migrants from Zimbabwe, India, and Ethiopia using semi-structured interviews. Data were analysed thematically. The study revealed that most migrants who reside in the rural areas of South Africa seldom experience xenophobic attacks, and therefore their livelihoods are not always negatively affected. The study concluded that displacement, deportation, and loss of income due to xenophobic attacks are experiences of undocumented migrants in the cities and not in the rural areas. This study also makes recommendations that migration management policies be implemented fully in the rural areas because this is where undocumented migrants find comfort.